Numerical and Experimental Study on the Hydrodynamic Performance of a Sloping OWC Wave Energy Converter Device Integrated into Breakwater - Taotao Tao; Zhengzhi Deng; Mengyao Li; Pengda Cheng; Wenbo Luo (Journal of Marine Science and Engineering)
This study presents numerical and experimental investigations on an oscillating water column (OWC) wave energy device integrated into a sloping breakwater. Regular waves were generated in a physical wave tank to investigate the hydrodynamic performance and extraction efficiency of the small-scale nested OWC device. Simultaneously, to complement various scenarios, numerical simulations were conducted using the open-source computational fluid dynamics platform OpenFOAM. The volume of fluid (VOF) method was employed to capture the complex evolution of the air–water interface, and an artificial source term (Forchheimer flow region) was introduced into the Navier–Stokes equations to replace the power take-off (PTO) system. By analyzing wave reflection properties, energy absorption efficiency, and wave run-up, the hydrodynamic characteristics of the inclined OWC device were explored. The comparison between the numerical and experimental results indicate a good consistence. A smaller front wall draft broadens the high-efficiency frequency bandwidth. For relatively long waves, increasing the air chamber width enhances energy conversion efficiency and reduces wave run-up. The optimal configuration was achieved with the following dimensionless parameters: front wall draft <semantics>a/h=1/3</semantics>, air chamber width <semantics>d1/h=2/9</semantics>, and slope <semantics>i=2</semantics>. Due to the sloped structure, when compared with a vertical OWC, long waves can more easily enter the chamber. This causes the efficient frequency bandwidth to shift towards the low frequency range, allowing more wave energy to be converted into pneumatic energy. As a result, wave run-up is reduced, enhancing the protective function of the breakwater.